Additions to Amanita (Amanitaceae, Agaricales) section Arenariae from south-western Australia - Davison, Elaine; Giustiniano, D.; Bougher, N.L.; McGurk, L.E.; Watkin, E.L.J. (CSIRO PUBLISHING, 2021)
A recent molecular phylogeny of Amanita recognises three subgenera and 11 sections. Members of subgenus Amanitina are characterised by amyloid spores and a mycorrhizal habit. Section Arenariae falls within this subgenus. Members of this section are known only from southern Australia; they are either sequestrate (secotioid) or agaricoid and lack clamp connections. We describe the following three additional secotioid species: Amanita arenarioides Bougher, E.M.Davison & Giustiniano, A. compacta Bougher, E.M.Davison & Giustiniano and A. pseudoarenaria E.M.Davison, Giustiniano & Bougher, which are separated on macroscopic appearance, spore shape and genetic sequences. We also describe two agaricoid species, namely, A. pupatuju E.M.Davison, Giustiniano, McGurk & E.L.J.Watkin, and A sabulosa E.M.Davison & Giustiniano, which are separated on bulb shape and genetic sequences. We provide expanded descriptions of A. arenaria (O.K.Mill. & E.Horak) Justo and A. griselloides D.A.Reid; we also synonymise A. dumosorum D.A.Reid with A. peltigera D.A.Reid. A revised diagnosis and description of section Arenariae is provided, together with a key to currently recognised member of this section.